Determinants Of Tote Bag Adoption Among University Students : Evidence From Indonesia - Estuariel, Paskalis Edgar; Maharani, Gabriella Angel; Rahma, Hanifa Aulia; Trianita, Laudya; Permadani, Safa Tiya (Journal of Development Economic and Social Studies, 2026)
The continued high use of single-use plastic bags among consumers poses a challenge to efforts to reduce plastic waste and promote sustainable consumption behaviors. This study analyzes the factors influencing students’ decisions to choose tote bags as an alternative to plastic bags and evaluates the role of economic and non-economic factors in driving changes in consumption behavior. The study employs a quantitative approach using a binary logistic regression model based on survey data from 122 students in Surakarta City, selected via random sampling. The variables analyzed include willingness to pay, practicality, environmental awareness, availability of plastic bags, and monthly expenses. The results indicate that practicality is the strongest factor increasing the probability of choosing a tote bag, followed by environmental awareness, which also has a positive and significant effect. Conversely, the availability of plastic bags at the point of purchase negatively and significantly affects tote bag usage. Meanwhile, willingness to pay and monthly expenditure do not significantly influence students’ decisions. These findings indicate that functional aspects and environmental awareness are more decisive than economic considerations in promoting the use of environmentally friendly products. Therefore, strategies to increase the use of tote bags should focus on strengthening environmental education and restricting access to plastic bags at retail outlets to support more sustainable consumption.